Analysis of customer perception regarding the effectiveness of fraud and dispute management of bKash Limited. - Rafi, Kazi Shahriar Al (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.